Model for evaluating the effectiveness of the educational activities of the class teacher - V. V. Nikolina; A. A. Loshchilova; S. I. Aksenov (Obrazovanie i Nauka, 2023)
Introduction. The relevance of the research topic is due to the importance of the role of a class teacher in international educational practice. At the present stage, the institution of class leadership exists in the territory of the post-Soviet space, in China, France and a number of other countries. In the United States, a special structure has been formed – the dean’s office, which deals with issues of education. In many countries, there are positions of an educator, who is freed from educational work, attached to classes, as well as a mentor, tutor, who performs the function of the class teacher. In conditions of political tension, the activity of the class teacher acquires a leading character, creating the basis for the consolidation of society, ensuring national security on the basis of national and universal values. The class teacher provides pedagogical support for the educational process, cooperation with all participants in educational relations, is a key person in education. The personal development of students and the effectiveness of the educational system of the school largely depend on the activities of the class teacher. The ambiguity and multifunctionality of the activity of the class teacher require an objective evaluation of his/her work. The evaluation of the effectiveness of the educational activities of the class teacher is an integral part of diagnosing the quality of educational activities at school. In this regard, there is the need to develop a model for evaluating the effectiveness of the educational activities of the class teacher and the possibility of its implementation in the conditions of an educational organisation.Aim. The aim of the study is the theoretical and methodological substantiation, development and testing of a model for evaluating the effectiveness of the class teacher.Methodology and research methods. The study was based on the methodology of personality-oriented, system-activity, integrative, criteria-level, acmeological, competency-based and integrated approaches. Theoretical methods (theoretical analysis, generalisation and systematisation, modelling), empirical methods (questionnaires, the method of expert evaluations) were used as research methods. The study was carried out in 5 educational institutions of the Nizhny Novgorod region, which are the bases for the training of future teachers and class teachers of the Minin University (Nizhny Novgorod).Results. As a result, a structural-functional model for evaluating the effectiveness of the class teacher’s educational activities was developed and substantiated as a way of comprehensive diagnostics of his/her professional activities, improving the quality of interaction with all participants in educational relations. The model is presented in the unity of the target, content, procedural-organisational and result-evaluative components. The results of testing the developed model for evaluating the effectiveness of the class teacher are presented.Scientific novelty. The scientific novelty consists in the development of a structural and functional model of a complex-differentiated expert evaluation of the effectiveness of the class teacher, reflecting the multidimensionality of his/her activities and including value-targets, an integrative criteria matrix, evaluation procedure, diagnostic tools, evaluation trajectories and technology of their construction, a mechanism for calculating the results that determine the effectiveness of the educational activities of the class teacher. The designed expert evaluation model forms the basis for the development of a methodology for evaluating the effectiveness of the class teacher.Practical significance. The designed model for evaluating the effectiveness of the class teacher’s educational activities can be used in the practice of educational organisations to develop a system for encouraging the activities of the class teacher, supporting his/her professional growth, creating individual professional development trajectories, analytical conclusions and examinations.